The London Classification of gastrointestinal neuromuscular pathology: report on behalf of the Gastro 2009 International Working Group. Issue 7 (25th June 2010) - Knowles, Charles H; De Giorgio, Roberto; Kapur, Raj P; Bruder, Elisabeth; Farrugia, Gianrico; Geboes, Karel; Lindberg, Greger; Martin, Joanne E; Meier-Ruge, William A; Milla, Peter J; Smith, Virpi V; Vandervinden, Jean Marie; et al.
Abstract : Objective: Guidelines on histopathological techniques and reporting for adult and paediatric gastrointestinal neuromuscular pathology have been produced recently by an international working group (IWG). These addressed the important but relatively neglected areas of histopathological practice of the general pathologist, including suction rectal biopsy and full-thickness intestinal tissue. Recommendations were presented for the indications, safe acquisition of tissue, histological techniques, reporting and referral of such histological material. Design: Consensual processes undertaken by the IWG and following established guideline decision group methodologies. Results and conclusion: This report presents a contemporary and structured classification of gastrointestinal neuromuscular pathology based on defined histopathological criteria derived from the existing guidelines. In recognition of its origins and first presentation in London at the World Congress of Gastroenterology 2009, this has been named 'The London Classification'. The implementation of this classification should allow some diagnostic standardisation, but should necessarily be viewed as a starting point for future modification as new data become available.